Mali : Technical Assistance Report-Mining and Petroleum Taxation (Diagnostic Assessment). (IMF Staff Country Reports; Country Report ;, 2015)
This Technical Assistance Report discusses key findings of the assessment of Mali's mining and petroleum taxation. It is highlighted that the transparency of the mining or petroleum sector in Mali could be improved through the online publication of agreements signed with operating companies and their feasibility studies. The establishment of a standardized framework for the economic analysis of mining and petroleum project feasibility studies would improve governance in the natural resources sector. It is also recommended to establish the ring-fencing principle in a revised Mining Code and in the draft Petroleum Code.